Exosomal miR-21a-5p mediates cardioprotection by mesenchymal stem cells. (June 2018) - Luther, Kristin M.; Haar, Lauren; McGuinness, Myc; Wang, Yang; Lynch IV, Thomas L.; Phan, Anh; Song, Yang; Shen, Zilong; Gardner, George; Kuffel, Gina; Ren, Xiaoping; Zilliox, Michael J.; et al.
Abstract: Though experimental, stem cell transplantation has the potential to improve the condition of the heart after myocardial infarction. It does so by reducing infarct size and inducing repair of heart muscle and its blood supply. Mesenchymal stem cells (MSC) have been found to be effective in pre-clinical animal models and clinical trials, but the mechanisms by which they induce cardioprotection and repair are still not fully understood. Small extracellular vesicles known as exosomes are now recognized to be key mediators of beneficial MSC paracrine effects, and the concept that they transfer miRNA to change gene expression in recipient cells is of current therapeutic interest. We present complete deep miRNA sequencing of MSC exosome cargo, and found that of several cardioprotective miRNAs, miR-21a-5p was the most abundant. Because miR-21a-5p is a well-known cardioprotective miRNA, we investigated the hypothesis that MSC exosomes can cardioprotect the heart by increasing the level of miR-21a-5p in recipient cardiac cells, thereby downregulating expression of the pro-apoptotic gene products PDCD4, PTEN, Peli1 and FasL in the myocardium. Using miR-21 mimic transfection and treatment with wild type and miR-21a knockout MSC exosomes, we confirmed that exosomal miR-21a-5p is transferred into myocardium and is a major cardioprotective paracrine factor produced by MSCs acting via synergistic activity on multiple pathways. The data supports that residual cardioprotective effect may be due to other ncRNA or protein cargo. In silico analyses support that MSC exosomes may also contribute to angiogenesis, cell proliferation and other aspects of cardiac repair. Highlights: MSC derived Exosomes efficiently transfer their cargo to H9C2 and NMVM cells and are cardioprotective in vitro The most prevalent miRNA, miR-21a-5p is transferred into cells in vitro and in vivo miR-21a-5p mediates most of the cardioprotection against MI in vivo miR-21a-5p targets four gene products involved in apoptosis or cell survival; PTEN, PDCD4, Peli1, FasL, and reduces apoptosis Results confirm that MSC-derived exosomes are paracrine regulators and produce strong effects based upon synergistic modulation of targets